Life History Proses Perubahan Diri Mantan Narapidana Residivis - Utama, Mega Kurnia; Dewi, Damajanti Kusuma (Jurnal Psikologi Teori dan Terapan, 2015)
The processs of changes among ex-recidivist convict is interesting issues in terms of how they face problems of living with society that impact on self-change. The purpose of this study was to explore the experience of an ex-recidivist convict in struggling to reintegrate into society. This research used qualitative approach with life-history method. One participant who is an ex-recidivist convict and two significant others were involved in this study.Â  Data collected using semi-structured interviews and analyzed using narrative analysis. This study reveals 4 (four) major themes, the participantâs life before his change, the participantâs self-transformation, the ways he takes to face the obstacles of change andÂ  social context of the Â changing process. In general, the result of this study shows that the participant has succeeded his changing process which is signed by the fact that he does not do any criminal acts or another negative behaviour anymore. The self-changing has been increased by the participant through his efforts to change his surrounding environment into the better condition.Â Abstrak: Penelitian ini dilatarbelakangi oleh bagaimana proses perubahan mantan narapidana residivis baik dari segi permasalahan yang muncul serta dampak perubahan diri pada individu. Penelitian bertujuan mengungkap bagaimana pengalaman partisipan terkait proses perubahan, cara partisipan dalam menghadapi hambatan, serta keadaan lingkungan sosial pada proses perubahan. Penelitian menggunakan pendekatan kualitatif dengan metode life history dengan analisis data naratif. Pengambilan data menggunakan metode wawancara semi-tersturktur yang terdiri dari 1 partisipan inti dan 2 orang significant other. Peneltian menghasilkan 4 tema besar yaitu kehidupan partisipan sebelum berubah, proses perubahan diri, cara menghadapi hambatan, kondisi lingkungan sosial dalam proses perubahan. Hasil secara umum menunjukkan bahwa partisipan berhasil dalam proses perubahannya yang ditandai tidak kembali melakukan tindakan kriminal ataupun perilaku negatif lainnya. Perubahan diri juga partisipan tingkatkan dengan usahanya dalam mengubah lingkungan.